Intervensi Non Farmakologis pada Pasien Diabetes Mellitus dengan Gangguan Tidur - Irmariani Irbar; Debie Dahlia; Denissa Faradita Aryani; Riri Maria (Jurnal Keperawatan Silampari, 2023)
This study aims to investigate the effects of non-pharmacological interventions in diabetes mellitus patients with sleep disturbances. The research method used was a systematic review with a randomized controlled trial (RCT) and quasi-experimental design. Article searches used five databases, Scopus, Proquest, ScienceDirect, Pubmed, and EbscoHost, published from January 2018 to December 2022. The results showed that eight articles met the criteria. Non-pharmacological interventions given to diabetes mellitus patients with sleep disorders include Cognitive Behavioral Therapy (CBT), Acceptance and Commitment Therapy (ACT), aromatherapy, personalized intervention, and nutritional therapy. Most studies report that non-pharmacological interventions can improve sleep quality in diabetes mellitus patients with sleep disorders. CBT therapy is the recommended therapy that is more effective. In conclusion, non-pharmacological interventions can be used as a companion or substitute therapy to improve sleep quality in patients with diabetes mellitus who experience sleep disturbances. Keywords: Diabetes Mellitus, Non-Pharmacological Intervention, Sleep Quality